2017
DOI: 10.2116/analsci.33.1297
|View full text |Cite
|
Sign up to set email alerts
|

Change in Plasma Total, Esterified and Non-esterified Capric Acid Concentrations during a Short-term Oral Administration of Synthetic Tricaprin in Dogs

Abstract: We studied change in the plasma total, esterified and non-esterified capric acid (FA10:0) and its effect on longer fatty acid concentrations during the short-term oral administration of synthetic tricaprin in dogs. We administered 150 and 1500 mg tricaprin/kg body weight per day orally to dogs for 7 consecutive days. Blood samples were collected at 0, 0.5, 1, 2, 4, 8, and 24 h on the 1st and 7th days for measuring the total-, esterified-and non-esterified-FA10:0. The total-FA10:0 concentration increased in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Based upon these data, the Osaka University Hospital manufactured GMP-graded capsules containing the active gradients called CNT-01. We developed the assay to measure plasma capric acid levels [52, 53]. After finishing toxicity tests using rats and dogs required, we are finally conducting investigator-initiated clinical trials.…”
Section: Academia-initiated Development Of Specific Treatment For Tgcvmentioning
confidence: 99%
“…Based upon these data, the Osaka University Hospital manufactured GMP-graded capsules containing the active gradients called CNT-01. We developed the assay to measure plasma capric acid levels [52, 53]. After finishing toxicity tests using rats and dogs required, we are finally conducting investigator-initiated clinical trials.…”
Section: Academia-initiated Development Of Specific Treatment For Tgcvmentioning
confidence: 99%
“…The serum sample preparation procedure was done in accordance to Shrestha et al as previously reported. 23 In brief, a portion of serum (25 lL for total FA, 100 lL for free FA) was spiked with the ISTD FA 11:0 (2 nmoL). For the total FA determination, saponification was performed by mixing the serum with 100 lL of 0.3 M KOH-EtOH and heating at 80 C for 45 min.…”
Section: Sample Preparationmentioning
confidence: 99%
“…And this method has been applied in our laboratory for determining medium-chain fatty acid (MCFA) and long-chain fatty acid (LCFA) of their total and free forms in various samples, ranging from the clinical blood sample to the commercial milk. [22][23][24] However, the strategy of HPLC with NPHderivatization was not applicable for SCFAs in our laboratory, due to the poor resolution and the interference in chromatography.…”
Section: Introductionmentioning
confidence: 98%
“…First, the overall time for the preparation of samples has been significantly reduced in the present method. In our previously published report, 22 the pretreatment of samples using the conventional heating method takes 80 min, which can be shortened to 160 s using microwave heating. The derivatization alone needs 20 min of heating at 60 C in the conventional method, which can be decreased to 10 s using MAD.…”
Section: Comparison With Conventional Methodsmentioning
confidence: 99%
“…21 We have successfully applied the UV-HPLC method to monitoring the change of free and esterified capric acid (FA10:0) in serum samples after the oral administration of synthetic tricaprin. 22 The HPLC assay of FA hydrazides has enabled simple, sensitive, and specific measurements of FA.…”
Section: Introductionmentioning
confidence: 99%